Effects of β-Alanine Dietary Supplementation on Concentration of Carnosine and Quality of Broiler Muscle Tissue - Gordana Kralik; Milan Sak-Bosnar; Zlata Kralik; Olivera Galović (The Journal of Poultry Science, 2014)
The research was carried out on 75 Cobb 500 broilers, which were divided into three groups. During the last three weeks of fattening broilers were fed finisher diets supplemented with β-alanine (P1=control group, P2=0.5% β-alanine and P3=1% β-alanine). The research objective was to evaluate effects of β-alanine supplemented to designed broiler diets on the quality of broiler muscle tissue and concentration of carnosine. After slaughtering, the following traits of muscle tissue quality were measured: initial and final pH value (measured 45 minutes after slaughtering pH1, and 24 hours after cooling pH2), drip loss, color (Minolta colorimeter, expressed as CIE L*, CIE a* and CIE b* values), softness of meat and cooking loss. Samples of breast and thigh muscle tissue were used for determination of moisture, fat, protein, collagen and carnosine. Intensity of lipid oxidation (TBARS) was determined in breast muscle tissue. Statistical analysis proved that supplementation of 1% β-alanine to broiler diets significantly lowered portion of collagen in thigh muscle tissue (P1=1.28% compared to P3=1.06%), while it increased cooking loss in breast muscle tissue (P1=24.23% compared to P3=33.29%). Supplementation of β-alanine to diets (0.5% or 1%) affected more intensive a* color in breast muscle tissue (P1=1.78 compared to P2=2.88 and P3=2.82). Analysis of results referring to concentration of carnosine in broiler tissue showed that supplementation of 1% of β-alanine increased concentration of carnosine in breast muscles from 756.15 μg/g of tissue (P1) to 911.01 μg/g of tissue (P3), while thigh muscle tissue exhibited significantly higher concentration of carnosine already within dietary supplementation of 0.5% of β-alanine (P1=371.78 μg/g of tissue compared to P2=540.29 μg/g of tissue and P3=526.83 μg/g of tissue; P<0.05). Feeding treatments and time of meat storage had no effect on TBARS values.